Desenvolvimento de um sistema de medição de vazão de ar por ventaneira no alto-forno A da ArcelorMittal Monlevade - Fabiano Cristeli de Andrade (2008)
Aiming to know the radial distribution of the air flow rate in the Blast Furnace A at ArcelorMittal Monlevade, a study was carried out about alternatives to install a trustworthy system of measurement air flow rate in the tuyere. The main available methodologies of measurement of fluid flow had been considered in the literature, amongst which the measurer Venturi, whom it technical showed to be most viable. It was elaborated a mathematical study and a physical analysis of the viability of implantation of this type of a measurer in the straight stretch named "down-leg" of thetuyere. An industrial test for validation of the study was carried out too.After the industrial test was verified that the value of air flow rate found in a tuyere was next to the waited mathematically. Moreover, the behavior of the air flow rate during the time showed a similar trend to the total air blown rate. With the implementation of the measurer Venturi in two others "down-legs" was perceived a good repeatability of developed system and, with this, to conclude that the developed system to measure the air flow rate in each tuyere in the blast furnace was trustworthy, easy and with lowcost implementation. After the implementation of this system in 22 tuyeres of the Blast Furnace A, foreseen to end of 2011, will be able to know the partition of the air flow rate in each quadrant of the Blast Furnace A and associate with hearth wear, skull formation and others blat furnace phenomena. Moreover, this system will be the base for implementation of a system of control of the amount of coal injected in each tuyere. The expectation of this project is to get an equal distribution of air and the coal injected in each tuyere allowing decrease the fuel ratewith an improvement in the gaseous flow inside of the blast furnace.